Teoria i praktyka etymologiczna Samuela Bogumiła Lindego na tle jego komparatystyki językoznawczej - Lewaszkiewicz, Tadeusz (Slavia Occidentalis, 2017)
Linde’s theory and practice of etymology must not be evaluated solely through the lens of modern linguistics, but also from the point of view of late 19th century language (especially Slavic language) studies. Against the general background of late 18th/early 19th century linguistics, his theory of etymology may be granted tentative approval, even though it contains many mistakes and nonsensical conclusions. Linde compiled the views of many of his predecessors (such as de Brosses, de Gébelin, Adelung, Ihre, Wachter and Dobrovský), but also attempted to modify some of their thoughts and add his own. It is not true (as stated in Zwoliński 1981) that no connection exists between the etymological theories of Dobrovský and Linde. The Polish lexicographer did indeed partially utilise the Czech’s work. Such approval cannot, however, be extended to Linde’s etymological practices as regards comparing Polish and Polish-Slavic lexical material: even though 65% (i.e. 547) of etymological fields contain correctly compiled vocabulary, mistakes occur in 35% (i.e. 292) of them. That Linde’s etymology-deriving principles were ineffective is evidenced by the fact that each of these 292 etymological fields should – based on the state of knowledge in the late 19th/early 20th century – be split into from 2 to 19 etymological fields. On the other hand, his etymological lists that cite words from many Indo-European languages, such as Polish and other Slavic languages, Latin, Greek, German and Baltic languages, and Sanskrit, should be viewed with some approval. Most of the comparisons found in Linde’s etymological treatise, which contains about 1,300 entries, bear similar marks of plausibility. The possibility of Bopp, Rask and Grimm being familiar with the inquiries of the Polish lexicographer and amateur linguist cannot be excluded. In the 19th century, Linde’s etymological principles influenced the so-called inspired linguists, including J. Kamiński, J. Lelewel, A. Mickiewicz and C.K. Norwid.